A7.21 The effect of extracellular vesicles on human in vitro osteoclastogenesis. (24th February 2016) - Marton, N; Kovács, OT; Baricza, E; Győri, D; Mócsai, A; Meier, F; Goodyear, C; McInnes, I; Buzás, E; Nagy, Gy
Abstract : Introduction: Extracellular vesicles (EV) are subcellular sized intercellular messengers, which are present in various biological fluids. EVs carry a wide variety of biomolecules and they may alter the recipient cells' functions. The microvesicles are plasma membrane derived EVs; the exosomes, the smallest vesicles, originate from the endosome. Our objectives were to investigate the effect of EVs on the human in vitro osteoclastogenesis, and to characterise the serum EV profile of healthy donors, rheumatoid arthritis (RA) and psoriatic arthritis (PsA) patients. Methods: Blood samples of healthy volunteers, RA patients and PsA patients with peripheral arthritis were collected into acid citrate dextrose vacutainer tubes. EVs were isolated by filtration and centrifugation. EV samples were stained with fluorescent anti-CD3, CD14, CD15, CD19, CD42b, CD235a antibodies (BioLegend) and detected by flow cytometry. CD14 + cells were extracted from PBMCs by using positive selection method (StemCell), and the cells were stimulated with 50 ng/ml recombinant human M-CSF for 24 hrs (PeproTech). Then the samples were treated with 50–50 ng/ml recombinant human M-CSF and RANKL (PeproTech) and with or without blood derived microvesicles or exosomes. After 7 days, the cells were fixed and stained for tartrate resistant acid phosphatase (TRAP) using a commercially available kit (Sigma) . TRAP-positive cells with at least 3 nuclei were considered as osteoclasts and counted by using the ImageJ software. Results: RA and PsA EV samples showed increased expression of lymphocyte markers (CD3, CD19) compared to healthy donor-derived EVs (n = 6). Microvesicles did not alter the number of mature osteoclasts. By contrast, exosomes significantly (p < 0.01) inhibited the osteoclast differentiation of the healthy (n = 10) and RA (n = 10) donor-derived monocytes, but not that of the PsA patients' monocytes (n = 7). Conclusion: Our present data suggest that the plasma profile of EVs might be altered in active arthritis compared to physiological condition, and exosomes or their cargo can regulate the human osteoclastogenesis.